Evaluating the Safety Profile of Semaglutide: An Updated Meta-Analysis - Rivera, Frederick Berro (Archīum Ateneo, 2024)
Background Semaglutide is increasingly used in the management of type 2 diabetes mellitus and obesity. Ensuring the safety of this medication is crucial for its clinical use. This meta-analysis evaluates the safety profile of semaglutide across patient populations and treatment durations. Methods Randomized controlled trials assessing the safety of semaglutide vs. placebo, with specified treatment durations were identified. The primary outcome was occurrence of any cardiovascular adverse events. Secondary outcomes included sudden cardiac death, adverse events leading to death, adverse events, gastrointestinal side effects, occurrence of hypoglycemia, and new-onset neoplasm. Results A total of 23 studies met the inclusion criteria with a combined sample size of 57,911 participants. The meta-analysis revealed that the adverse event associated with semaglutide is gastrointestinal in nature (nausea and vomiting). No significant differences were observed between semaglutide and comparator groups. Conclusion Semaglutide appears to have a favorable safety profile across diverse patient populations and treatment durations, supporting its continued use in the management of type 2 diabetes mellitus and obesity. It is generally well-tolerated, with a low incidence of adverse events. Clinicians should be aware of these findings and monitor patients accordingly. Further long-term studies are warranted to assess the safety of semaglutide in clinical practice.